PERAN SIKAP DALAM MEMEDIASI PENGARUH KESADARAN LINGKUNGAN TERHADAP NIAT BELI PRODUK RAMAH LINGKUNGAN - Laksmi, Alit Devi; Wardana, I Made (E-Jurnal Manajemen, 2015)
Environmental issues become a very important issue in Indonesia such as deforestatio, industrial waste pollution, air pollution, and decreased quality of biodiversity. This condition causes changes in the behavior of people who are becoming concerned about the environment and switch to using environmentally friendly products. The purpose of research to examine the role of mediating variables influence attitudes towards environmental awareness and purchase intent AC Sharp-friendly neighborhood in the city of Denpasar. This research was conducted in the city of Denpasar. Probability sampling using is sampling methods. Data was collected through questionnaires. Respondents of the study were 100 respondents. Data analysis techniques used in this research is the analysis of pathways and Sobel test. These results indicate that environmental awareness has a positive and significant impact on consumer attitudes, awareness of the environment has a positive and significant impact on purchase intention, consumer attitudes have a positive and significant effect on purchase intentions, and attitudes significantly mediate the indirect effect to the intent of environmental awareness Sharp buy environmentally friendly air conditioning in Denpasar.
Keywords: environmental awareness, attitudes, and purchase intentions